2021
DOI: 10.1097/mph.0000000000002206
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Pegteograstim on Chemotherapy-induced Neutropenia in Children and Adolescents With Solid Tumors

Abstract: Purpose: Pegteograstim (Neulapeg) is a recombinant human granulocyte colony-stimulating factor conjugated with methoxy-maleimide-polyethylene glycol. We conducted a single-arm study investigating its safety and noninferiority to conventional filgrastim in children and adolescents Materials and Methods: Patients younger than 21 years with solid tumors were eligible for the study. Pegteograstim was administered on day 7 of the fourth chemotherapy cycle. Toxicities were monitored, and the change in absolute neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Nowadays, besides filgrastim and lenograstim, eight major G-CSF drugs are known: long-acting filgrastim-pegfilgrastim, lipegfilgrastim, mecapefilgrastim [14], empegfilgrastim [15], S/L-G-CSF biosimilar-balugrastim [16], leridistim, pegleridistim [17], and pegteograstim [18].…”
Section: Pharmaceutical Variantsmentioning
confidence: 99%
“…Nowadays, besides filgrastim and lenograstim, eight major G-CSF drugs are known: long-acting filgrastim-pegfilgrastim, lipegfilgrastim, mecapefilgrastim [14], empegfilgrastim [15], S/L-G-CSF biosimilar-balugrastim [16], leridistim, pegleridistim [17], and pegteograstim [18].…”
Section: Pharmaceutical Variantsmentioning
confidence: 99%
“…8 Previous studies demonstrated its cost-effectiveness, safety, and comparable efficacy to conventional rhG-CSF for the management of CIN in adults, 9 children, and adolescents. 10,11 Pegfilgrastim, a PEGylated form of rhG-CSF (analog of filgrastim), was approved for use in children to reverse CIN and reduce the incidence of neutropenia-associated infections. 12,13 Although PEG-rhG-CSF (Brand name, Jinyouli) was approved for marketing in China in March 2012, its use has been limited to Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the plasma half‐life of PEG‐rhG‐CSF could be extended to up to 47 h, with preserved solubility, bioavailability, and stability 8 . Previous studies demonstrated its cost‐effectiveness, safety, and comparable efficacy to conventional rhG‐CSF for the management of CIN in adults, 9 children, and adolescents 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation